Inisiasi Ecopreneurship bagi Generasi Muda: Implementasi Ecoprint Pounding Berwawasan Green Economy: Ecopreneurship Initiation for the Young Generation: Implementation of Ecoprint Pounding with a Green Economy Perspective - Irsan Kadir; Lukman Ismail; Soekarno Buchary Pasyah; Muh. Haerul Surya; Yuni Delima; Nur Fitrah Ramadhani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The Muhammadiyah Sejati Makassar Orphanage faces the complex task of achieving operational autonomy, especially given its significant dependence on external donations and the inadequate life skills of its foster children. This issue requires empowerment initiatives that realistically equip individuals with vocational skills. This initiative, through the community service program, seeks to empower foster children by providing training in ecoprint creative arts skills that have significant commercial value and support environmental sustainability. The implementation method uses the Asset-Based Community Development (ABCD) approach through a participatory training model, which includes socialization stages, technical training on ecoprint pounding using tote bags and local leaves such as balakacida leaves (Chromolaena odorata), red castor leaves (Jatropha gossypiifolia), and papaya leaves (Carica papaya), as well as product monitoring and evaluation. This activity successfully produced tote bags and scarf fabrics with aesthetically pleasing, commercially valuable motifs and significantly improved the trainees' hard skills in scoring, mordanting, pounding, and fixation. This program not only produces physical product outputs but also strategically develops soft skills by fostering an entrepreneurial spirit (ecopreneurship) and promoting awareness of the green economy, becoming an important asset for the economic independence of partners in the future. Methodology, results, and conclusions, but do not need to make these words explicit. Abstracts must not contain tables/figures and must not include citations. It is not permitted to use abbreviations except for units of a quantity and to use them to a minimum.